2003
DOI: 10.1177/021849230301100204
|View full text |Cite
|
Sign up to set email alerts
|

Total Arterial Revascularization on Beating Heart: Experience in 803 Cases

Abstract: To avoid the deleterious effects of cardiopulmonary bypass, total arterial revascularization was performed on the beating heart, using an Octopus stabilizer, in this prospective study of 803 patients without selection bias. Single-vessel disease was present in 71 (9%) patients, double-vessel disease in 204 (25%), and triple-vessel disease in 528 (66%). An ejection fraction < 30% was found in 127 (16%) cases. Angiography was carried out before discharge in 204 (25%) patients. Grafts included left and right inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 20 publications
1
4
0
2
Order By: Relevance
“…PUSKAS et al carried out a randomized trial comparing both techniques with complete revascularization (approximately 3.4 grafts per patient in both groups) and showed that patients undergoing elective offpump coronary artery bypass presented lower levels of myocardial injury, less transfusion requirements and shorter hospital stays [14]. In our series, we carried out total revascularization with the exclusive use of multiple arterial conduits and obtained the same results with regards to technical feasibility and procedural morbidity and mortality as the ones presented by SINGH et al [15]. Not manipulating the ascending aorta could be one of the factors which explain the low incidence of postoperative cerebral problems.…”
supporting
confidence: 67%
“…PUSKAS et al carried out a randomized trial comparing both techniques with complete revascularization (approximately 3.4 grafts per patient in both groups) and showed that patients undergoing elective offpump coronary artery bypass presented lower levels of myocardial injury, less transfusion requirements and shorter hospital stays [14]. In our series, we carried out total revascularization with the exclusive use of multiple arterial conduits and obtained the same results with regards to technical feasibility and procedural morbidity and mortality as the ones presented by SINGH et al [15]. Not manipulating the ascending aorta could be one of the factors which explain the low incidence of postoperative cerebral problems.…”
supporting
confidence: 67%
“…32,33 Recent infarctions, redo surgery and intramyocardial vessels are also no longer limiting factors for the technique. 32,33 Recent infarctions, redo surgery and intramyocardial vessels are also no longer limiting factors for the technique.…”
Section: Indications and Limitsmentioning
confidence: 99%
“…A la espera de la publicación escrita definitiva de las conclusiones y recomendaciones de la Conferencia de Consenso ISMICS 2004, que se espera para los próximos meses, se puede afirmar en la actualidad que hay consenso en que: «la cirugía coronaria sin CEC es segura y efectiva, y no hay diferencias significativas en la mortalidad con la cirugía coronaria convencional en las series con pacientes de variado riesgo. Se puede conseguir una revascularización completa con ambas técnicas [53][54][55] , sin diferencias significativas en los estudios con pacientes de variado riesgo. No hay diferencias significativas en los resultados clínicos 56 , angiográficos precoces [53][54][55] y a los 6-12 meses entre ambas técnicas [57][58][59][60] .…”
Section: Conferencia De Consenso Ismics 2004unclassified